Reposisi Badan Kehormatan Dewan Perwakilan Rakyat Daerah Dalam Menjaga Kedisiplinan Dan Kinerja - Widyasari Rifki, Ika; Sudarmanto, Kukuh; Arifin, Zaenal (Universitas Semarang, 2023)
TThe purpose of this study is to examine how the Ethics Council as a complement to the DPRD in order to maintain dignity and honor in accordance with the DPRD's code of ethics. In fact, the Ethics Council is expected to play a role not only as a guardian of the morale and integrity of DPRD members, but also as an internal mechanism for enforcing the code of ethics and maintaining discipline, ethics and board performance. In this study using the type of empirical research. Because the title raised refers to the Reposition of the Honorary Board of the Regional People's Legislative Assembly of the Temanggung Regency in Maintaining Discipline, Ethics and Council Performance in the Regional DPRD of Temanggung Regency. The renewal of this research has not yet examined the repositioning of the Honorary Board of the Temanggung Regency People's Representative Council in maintaining discipline and performance of the council. The importance of the legal system and subsystem in taking action and maintaining the discipline of DPRD members is an important tool in monitoring and prosecuting violations of the code of ethics. Tujuan penelitian ini untuk mengkaji bagaimana Badan Kehormatan sebagai alat kelengkapan DPRD dalam rangka menjaga martabat dan kehormatan sesuai dengan kode etik DPRD. Padahal, Badan Kehormatan diharapkan berperan tidak hanya sekedar menjadi penjaga moral dan integritas anggota DPRD, melainkan juga menjadi mekanisme internal untuk menegakkan kode etik serta menjaga Kedisiplinan, Etika Dan Kinerja Legislatif. Dalam penelitian ini menggunakan jenis penelitian empiris. Sebab dari judul yang diangkat mengacu kepada Reposisi Badan Kehormatan Dewan Perwakilan Rakyat Daerah Kabupaten Temanggung Dalam Menjaga Kedisiplinan, Etika Dan Kinerja Legislatif di Wilayah DPRD Kabupaten Temanggung. Kebaharuan penelitian ini belum ada yang meneliti tentang Reposisi Badan Kehormatan Dewan Perwakilan Rakyat Kabupaten Temanggung dalam menjaga kedisiplinan dan kinerja legislatif. Pentingnya sistem dan subsistem hukum dalam suatu penindakan serta menjaga kedisiplinan anggota DPRD merupakan suatu perangkat yang penting dalam pengawasan dan penindakan pelanggaran kode etik.